2006
DOI: 10.1007/s10450-006-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

New method for evaluation of heavy metal binding to alginate beads using pH and conductivity data

Abstract: Extensive research has been conducted for removal and recovery of heavy metals from wastewater and industrial wastewater in recent years. Due to its low cost and high sorption efficiency, alginate was extensively investigated as a biosorbent. It is known that the sorption of metals to alginate is rate limited. However, the sampling in the beginning of experiments, from 30 seconds to few minutes, is very difficult, if not impossible. In this study, a nontraditional experimental method was used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This applies more to the DW_PM system, where a positive correlation was found between the amount of adsorbed metal ions and the amount of released iron ions. Studies on the relationship between the physical parameters of various metal ions, including toxic metal ions, and the binding affinity of these metal ions for alginate, have shown that Pb 2+ , Cd 2+ , Cu 2+ and Zn 2+ have higher affinity to alginates in comparison to Fe 3+ [ 47 , 48 ]. In the DW_PM solution, the ionic exchange between metal ions and Fe 3+ was four times greater than in the SW_PM solution, which is indicated by a much greater amount of released Fe 3+ ions in the DW_PM solution.…”
Section: Discussionsupporting
confidence: 90%
“…This applies more to the DW_PM system, where a positive correlation was found between the amount of adsorbed metal ions and the amount of released iron ions. Studies on the relationship between the physical parameters of various metal ions, including toxic metal ions, and the binding affinity of these metal ions for alginate, have shown that Pb 2+ , Cd 2+ , Cu 2+ and Zn 2+ have higher affinity to alginates in comparison to Fe 3+ [ 47 , 48 ]. In the DW_PM solution, the ionic exchange between metal ions and Fe 3+ was four times greater than in the SW_PM solution, which is indicated by a much greater amount of released Fe 3+ ions in the DW_PM solution.…”
Section: Discussionsupporting
confidence: 90%
“…Encapsulation unfavoured the sorption since the highest rate constants were observed for Namont. A double mechanism of diffusion in the gel structure and ion exchange was proposed to describe the kinetic of sorption of metals [18,19,24].…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…We found the pH value of the solutions changed from 3.0 to 2.24 for Cr (III) and 2.19 for Ni (II), and from 4.0 to 3.11 for Cu (II), 3.20 for Co (II) and 3.14 for Zn (II), respectively. These results indicated that the mechanism probably involves the competitive adsorption of H + with metal ions for the exchange site in the system [34,35]. In order to ensure quantitative adsorption and avoid precipitation at higher pH values, pH 4.0 was chosen as the optimum pH for further studies.…”
Section: Effect Of Phmentioning
confidence: 98%